DESIGN OF LEARNING APPLICATION SYSTEM TO KNOW INDONESIAN LANGUAGE OBJECTS FOR EARLY CHILDHOOD EDUCATION - Ilham Pratama; Volvo Sihombing; Ibnu Rasyid Munthe (INFOKUM, 2021)
Today, along with the times, which are supported by the rapid development of technology, all aspects of life cannot be separated from the influence of technology. The research was conducted to try to conduct research with the aim of examining more deeply what ingredients can be said to be harmful in food, how the performance of BBPOM in determining these hazardous materials, and how BBPOM will follow up if it has been found that some foods containing hazardous ingredients have been found. and what steps are taken to minimize the use of these hazardous materials in order to maintain the health of consumers. In drawing conclusions in expert systems, Forward Chaining and Backward Chaining are generally used. However, with the use of these two reasons, it is not possible to determine the value of confidence in the hypothesis. Based on the research conducted, it was found several things that can be observed in the development of uncertainty consultation media in the identification of formalin and borax in meatballs, namely the following, including the existence of an expert system with the certainty factor method, so that people can find out the characteristics of formalin meatballs without meeting directly with expert doctors or the expert. Likewise for designing expert system applications to identify food hazards in Formalin and Borax can use Visual Studio 2010 Applications Based on the research conducted, it was found several things that can be observed in the development of uncertainty consultation media in the identification of formalin and borax in meatballs, namely the following, including the existence of an expert system with the certainty factor method, so that people can find out the characteristics of formalin meatballs without meeting directly with expert doctors or the expert. Likewise for designing expert system applications to identify food hazards in Formalin and Borax can use Visual Studio 2010 Applications Based on the research conducted, it was found several things that can be observed in the development of uncertainty consultation media in the identification of formalin and borax in meatballs, namely the following, including the existence of an expert system with the certainty factor method, so that people can find out the characteristics of formalin meatballs without meeting directly with expert doctors or the expert. Likewise for designing expert system applications to identify food hazards in Formalin and Borax can use Visual Studio 2010 Applications